PENGEMBANGAN INSTRUMEN PENILAIAN DALAM PENDIDIKAN MATEMATIKA REALISTIK INDONESIA (PMRI) DI SMPN 17 PALEMBANG - Tuti Rahayu; Purwoko Purwoko; Zulkardi Zulkardi (Universitas Sriwijaya, 2008)
This study aims to develop assessment instruments in Indonesian version of Realistic Mathematics Education (PMRI) with the topic special quadrilateral including the aspect of validity, of practicality, and of the effectivity. The methodology that use in this study is a developmental research. This form of research consists of self evaluation and prototyping. The subject of this study is 32 students of the first grade of SMPN 17 Palembang. Experts review, and documentary analysis were used incollecting data. For evaluating process, observation sheet, learning log, the use of student’s strategy and solution from the result of their achievement. The collected data were analyzed using qualitative descriptive. The findings show that assessment instruments in PMRI in the topic special quadrilaterals could be categorized as valid, practical, and effective. The validity is measured by using the aspects of contents, contruction, and language based on assessment’s principles of PMRI. Based on the experts coments, the assesement instruments developed can be practically in the teaching learning process. According to the observer , the observation sheet and learning log show that students are motivated to be individual or group in doing the exercises. The effectivity is analyzed operationally that is to see student’s ability when the instruments are trying out including the process and the products. Students can argue either orally or writen. Key words : Developing research, instruments, assessment